STRATEGI PERANCANGAN KAWASAN BENTENG VASTENBURG SEBAGAI MUSEUM KOTA SURAKARTA DENGAN PENDEKATAN INFILL DESIGN - Hildaria Putri Lestari Siregar; Kusumaningdyah Nurul Handayani; Hari Yuliarso (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
Vastenburg Fortress is a fortress of Dutch army built within Sala village in 1832. As time goes on, the building stands by as 'silent witness' of every steps of social dynamics in Surakarta. Therefore, the fortress shows important potencies for society development in future. Based of the mapping of those existing potencies, the design potencies is to create a place that able to experimentally connect new significancy between future society development and all historical components within the site. Hence, the new function as urban museum does really fit in this category. To adapt with the new function as urban museum, using infill design as the main design approach is supported by several design methods; earth-sheltered architecture, sequence concept. Infill design is the main approach to integrate the old elements and the new elements within the site. Earth-sheltered architecture is the structural approach of the design that fits the site condition with its historical elements. Sequence concept is the basic concept of integrating the site with other heritage areas around it.